Functional English and Chinese as mediums of instruction in a higher institution in Hong Kong - Xu, Zhichang (Springer, 2014)
Hong Kong Special Administrative Region (HKSAR) is a vibrant multilingual society whose official language include Chinese and English. The language policy of Hong Kong calls for biliteracy (Chinese and English) and trilingualism (Cantonese, Putonghua and English), reflecting its complex multilingual situation. In this chapter, I shall review the multilingual language policies of Hong Kong, and issues regarding the medium of instruction (MOI) in the educational context with focus of the tertiary sector. I shall analyze two courses offered in one of the eight government-funded higher education institutions (HEIs) and discuss issues of functional English and Chinese as the MOI in alignment with the local institutional language policy. I argue that in multilingual societies, higher education institutions should make language policies compliant with the regional language-in-education policies, and adopt models of MOI that align with the realities of linguistically diverse teaching and learning communities.